Corporate Social Responsibility for Packet One Networks: Study, Analysis and Framework - Karthikeyan Selvakumari, Dhinesh Raj (2008)
The word culture is overused and overworked, especially in the context of companies. Yet corporate culture is a product of people, including a corporate culture that champions social responsibility. In the world of globalization, there has been a growing need to efficiently compete internationally for global emerging economies. Malaysia is not an exception as the country being considered as a rising economy with robust regulatory and legal framework. The development of CSR in Malaysia has, over time, moved to higher levels and Malaysia is recognised as being among the most active emerging economies in relation to corporate responsibility. Many would agree that sound CSR policies and corporate governance in the global markets are imperative to national economic welfare as well as to the stability of a global economic environment. "Malaysia is one of the leading countries in CSR, certainly among developing countries and in Southeast Asia." (Dr. Williams, 2008). Malaysia is required to build strategies to raise the level of CSR consciousness amongst corporate. They also require strategies to increase the capacity and capability to combat environmental and social concerns – in short to promote responsible businesses that head towards sustainable development. Malaysia vision of achieving developed country status in the year 2020 using Information and communication technology (ICT) sector as the vehicle, enabled organizations to invest more in the businesses related to ICT. The market opportunities for corporate social responsibility and the ICT industry are brighter than ever with increased awareness, initiatives, and support from all parties. IDC (2008) “predicts that corporate social responsibility and the ICT industry will drive one another to new heights in the coming years, creating a strong foundation for IT spending in order to improve corporate governance”. This management report on CSR is prepared for Packet One Networks (P1), the subsidiary of Green Packet Sdn. Bhd. The study has been carried both in internal and external of the firm and results have been discussed in the report based on the interviews conducted among employees and with identified stakeholders, finally report ends up in developing CSR framework that has been suggested for the company to adopt in immediate future.